Analysis of the resistance of M. tuberculosis to fluoroquinolon and the implementation of nuclear based biomolecular technique. - Mukh Syaifudin; Dewi Septiani (Indonesian Journal of Pharmacy, 2011)
Tuberculosis (TB) is still a problem in community health with high rate of mortality.  The  case  became  much  more  complicated  due  to  emerge  of Mycobacterium  tuberculosis which  are  resistant  to  the  drugs.  This  caused  the movement  of  attention  from  the  first  line  drugs  to  fluoro-quinolon  (FQ)  as alternative drug. The aim of this research was to do analysis the mutation which causing  the  resistance  of  bacterial  through  nucleic acid  alterations  with polymerase  chain  reaction  (PCR)  and  single  strand  conformation  polymorphism (SSCP)  technique.  Analysis  was  done  on  gyrA  and  gyrB  genes  encoding  DNA gyrase of bacterial and closely related to FQ resistance in 100 of sputa samples of  positive  BTA  test  results.  DNA  of  M.  tuberculosis strain  H37Rv  was  used  as control. From analysis on gyrA gene it was known that 57 samples were positive PCR  and  no  resistant  sample  was  found.  For  gyrB  gene,  only  12  of  them  were positive  PCR  and  again  there  was  no  samples  had  mutation  as  cause  of resistance.  These  mean  that  FQ  could  be  used  as  replacement  drug.  Molecular detection  technique  was  known  fast  and  specific  for assessing  bacterial resistance.  Researcher  proves  that  searching  for  P32-radioisotope  labeled  DNA alteration  was  more  sensitive.  Hopefully  this  results  of  experiment  can  be implemented  in  medication  with  more  effective  and  support  diagnose  results so that it will lowering the risk of patient mortality.Key words : M. tuberculosis, fluoro-quinolon, resistance, PCR, SSCP